Metasurface-based total internal reflection microscopy - Gortari, Antu Nehuen (Biomed Opt Express, 2020)
Recent years have seen a tremendous progress in the development of dielectric metasurfaces for visible light applications. Such metasurfaces are ultra-thin optical devices that can manipulate optical wavefronts in an arbitrary manner. Here, we present a newly developed metasurface which allows for coupling light into a microscopy coverslip to achieve total internal reflection (TIR) excitation. TIR fluorescence microscopy (TIRFM) is an important bioimaging technique used specifically to image cellular membranes or surface-localized molecules with high contrast and low background. Its most commonly used modality is objective-type TIRFM where one couples a focused excitation laser beam at the edge of the back focal aperture of an oil-immersion objective with high numerical aperture (N.A.) to realize a high incident-angle plane wave excitation above the critical TIR angle in sample space. However, this requires bulky and expensive objectives with a limited field-of-view (FOV). The metasurface which we describe here represents a low cost and easy-to-use alternative for TIRFM. It consists of periodic 2D arrays of asymmetric structures fabricated in TiO(2) on borosilicate glass. It couples up to 70% of the incident non-reflected light into the first diffraction order at an angle of 65° in glass, which is above the critical TIR angle for a glass-water interface. Only ∼7% of the light leaks into propagating modes traversing the glass surface, thus minimizing any spurious background fluorescence originating far outside the glass substrate. We describe in detail design and fabrication of the metasurface, and validate is applicability for TIRFM by imaging immunostained human mesenchymal stem cells over a FOV of 200 µm x 200 µm. We envision that these kinds of metasurfaces can become a valuable tool for low-cost and TIRFM, offering high contrast, low photodamage, and high surface selectivity in fluorescence excitation and detection.